(untitled) (Eurasian Research Bulletin, 2023)
It has been developed to find the mechanism of immobilization of the bismutol-2 Reagent to the carrier and to determine the optimal conditions and metrological properties of their formation of a complex with the rhenium (III) ion. The developed sorbtsion – spectroscopic method was applied to Real objects (industrial waste technological water and cakes), the results were processed by the method of Mathematical Statistics and information about its application in the analysis.